Numerical modeling of detection in contacts of bismuth-antimony alloy with different materials: influence of contact area and material factor - Cherner, Iacov (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2014)

(untitled)
Diode detectors (DDs) are widely used in electronic information and communication systems. In this paper, the numerical modeling of the electrical potential distribution and current passing in contacts of a normal metal or a superconductor with a bismuth-antimony (Bi Sb) semiconductor alloy is conducted. The possibilities of designing DDs based on these contacts to operate at the liquid helium temperature (T) of 4.2 K are explored. The dependences of current responsivity (CR), voltage responsivity (VR), and noise equivalent power (NEP) on the signal frequency (f) are analyzed. The role of the contact area is discussed. The contacts of Bi Sb with different materials are analyzed. The obtained results are compared to the literature data. Both DDs operating at the temperature of liquid nitrogen (T = 77.4 K) and liquid helium are considered. Comparison with existent literature data shows that the proposed DDs can be 10 100 times better. The physical reasons for these advantages are discussed. It is shown that the unique properties of Bi Sb alloys, particularly of a Bi0.88Sb0.12 alloy, make these alloys promising materials for cryoelectronics